2014
DOI: 10.1111/1469-0691.12805
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of treatment strategies for initial Clostridium difficile infection

Abstract: Clostridium difficile infection (CDI) is costly. Current guidelines recommend metronidazole as first-line therapy and vancomycin as an alternative. Recurrence is common. Faecal microbiota transplantation (FMT) is an effective therapy for recurrent CDI (RCDI). This study explores the cost-effectiveness of FMT, vancomycin and metronidazole for initial CDI. We constructed a decision-analytic computer simulation using inputs from published literature to compare FMT with a 10-14-day course of oral metronidazole or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 56 publications
0
64
0
3
Order By: Relevance
“…Endoscopic delivery carries some procedural risk and increases health care utilization and costs, though a cost-effectiveness study showed FMT dominated (i.e. was less costly and more effective) than vancomycin for initial CDI 42 . FMT is reported to be effective by all of these routes, and the preferred method may vary with the clinical situation.…”
Section: Current Treatment Guidelines and Methodsmentioning
confidence: 99%
“…Endoscopic delivery carries some procedural risk and increases health care utilization and costs, though a cost-effectiveness study showed FMT dominated (i.e. was less costly and more effective) than vancomycin for initial CDI 42 . FMT is reported to be effective by all of these routes, and the preferred method may vary with the clinical situation.…”
Section: Current Treatment Guidelines and Methodsmentioning
confidence: 99%
“…In published cost-effectiveness studies of oral vancomycin in the United States, the per-dose cost varies from $5 to $33 [2, 10]. Although it almost uniformly overestimates true acquisition costs, average wholesale price (AWP) is the only published reference that has been available for several years as a means of comparing vancomycin costs over time (Table 1).…”
Section: Cost Of Oral Vancomycinmentioning
confidence: 99%
“…Interestingly, endoscopic FMT is more cost-effective than treatment with vancomycin for initial CDI. 92 …”
Section: Fecal Microbiota Transplantmentioning
confidence: 99%